Stigma as a barrier to early intervention among youth seeking mental health services in Ontario, Canada: a qualitative study - Natasha Y. Sheikhan; Jo L. Henderson; Tanya Halsall; Mardi Daley; Samantha Brownell; Jai Shah; Srividya N. Iyer; Lisa D. Hawke (BMC, 2023)
Abstract Background Stigma associated with mental health challenges is a major barrier to service seeking among youth. Understanding how stigma impacts service-seeking decisions from the perspectives of youth remains underexplored. Such research is necessary to inform effective stigma reduction. Objective This study aims to understand how stigma influences service seeking among youth with mental health challenges. Methods Qualitative inquiry was taken using youth engagement, underpinned by pragmatism. Data were collected via 4 virtual focus groups with 22 purposively selected youth participants with lived experience of mental health challenges in Ontario, Canada. Focus group guides were developed collaboratively among research team members, including youth co-researchers. Data were analyzed inductively using reflexive thematic analysis. Results Three main themes were constructed from the data: point of entry into the system, being biomedicalized or trivialized, and paving the way for non-stigmatizing services. Initial contact with the mental healthcare system was seen to be affected by stigma, causing participants to delay contact or be refused services if they do not fit with an expected profile. Participants described a constant negotiation between feeling 'sick enough' and 'not sick enough' to receive services. Once participants accessed services, they perceived the biomedicalization or trivialization of their challenges to be driven by stigma. Lastly, participants reflected on changes needed to reduce stigma's effects on seeking and obtaining services. Conclusion A constant negotiation between being 'sick enough' or 'not sick enough' is a key component of stigma from the perspectives of youth. This tension influences youth decisions about whether to seek services, but also service provider decisions about whether to offer services. Building awareness around the invisibility of mental health challenges and the continuum of wellness to illness may help to break down stigma's impact as a barrier to service seeking. Early intervention models of care that propose services across the spectrum of challenges may prevent the sense of stigma that deters youth from accessing and continuing to access services.